Analysis of the Role of Class 5 Teaching Campus in Increasing Literacy and Numeracy at Mursyidah Elementary School - Febrianti, Putri Eka (BRIDGE : The Multidisciplinary Research Portal, 2023)
The Teaching Campus is a program initiated by the Ministry of Education and Culture as one of the flagship programs of the Independent Learning Campus Merdeka (MBKM) program. The Teaching Campus is a program that provides opportunities for students to study outside of lectures. (Sarma Panggabean, 2022) One of the main objectives of the Teaching Campus is to provide opportunities for students to participate in efforts to improve literacy skills in Indonesia. Open to students from all over Indonesia, and the Teaching Campus offers students to go directly to underdeveloped schools from across the archipelago. The Teaching Campus Program Batch 5 is part of the Merdeka Learning Campus program, which involves students from various campuses and majors to participate in the teaching and learning process at school. It provides opportunities for students to learn and develop themselves with activities outside of lectures. (Fatonah et al. al., 2021) The Teaching Campus program lasts approximately four months, from February 20 to June 12, 2023. The implementation of the Teaching Campus program focuses on literacy, numeracy, technology adaptation, and assisting school administration. Students assist students, especially grade 5 of Mursyidah Surabaya Private Elementary School, with 250 students. The purpose of Teaching Campus 5 is that apart from helping the school, it also helps students to continue to hone their potential, skills and develop themselves through activity opportunities outside of lectures.